Narrativas da sexualidade e suas prescrições revistas - Pereira, Caroline Suellen Cardoso (2010)
This research investigates the construction of meaning rendered by the kind of presence of females, males and social based on interaction between the subjects of enunciation and statement, in an attempt to answer the problem of the proposed research: how the press media standardizes the women semblance in contemporaneity? The contemporary women's identities are highlighted in research through the woman semblance installed in verbal texts, visual and spatial of the covers from Claudia, Creative, Marie Claire and Nova Magazines. It starts from the assumption that there is a semblance of sexualized woman in all of them, from which each magazine will accomplish it by means that define it in the publishing market. This study s path was founded on the theoretical and methodological framework of semiotic discourse, built by Algirdas Julien Greimas and his associates. The corpus of the research was determined in the years 2007, 2008 and 2009, with the selection and clipping, set from the exploration of themes, figures of speech and the contents that were treated by their reiterations plastic and isotopic that evidence the choices of the announcer on how spell out to your readers. On this focus the covers were subjected to a comparative method in order to identify, through discursive interaction established between enunciating and enunciatee installed, the differences in the way to treat of the sexuality. The main objective was thus to seize the various visibilities pictured, with their different attendance at the meeting of the subjects imagery that arises and allows showing which state of the presence of a contemporary woman that the press media holds. Specifically, the objective was to understand the generative pathway of the sense of covers as subjects of communication and meaning with their modal cognitive doings (knowledge and power), performers (to do) volitional (willing), identity (being), which circulate as forms of life and appeal to be operationalized by the enunciatee. We explored how the effects of sense of formants plastics eidetic, topological, chromatic and of matter structure the aesthetic and ethical dimensions of the press media, with its particular aesthetical formula of to make feel their prescriptions through operations of manipulation by the seduction. We identified the existence of an invariant semblence from a performative competence of the sexuality that the press media assumes in the interactive relationship with the enunciator and the manner of conducting its regulation, thus defining the set of variants that shape the nuances responsible for targeting the public. The specifications of the modes of presence argumentative, precise way, indicative, intuitive way guarantee the existence of semiotics of interlocutors who, likely the celebrities parades on the covers, in which we find the ways of being the women who populates the collective imagination